E-learning: Lessons out loud - Schmidt, Cliff (Technical Centre for Agricultural and Rural Cooperation, 2011)
The Talking Book, a robust handheld audio computer, records locally produced agricultural and literacy information for Ghanaian farmers to play back in their own language.